2002
DOI: 10.1021/np010535l
|View full text |Cite
|
Sign up to set email alerts
|

New Eremophilenolides from Ligulariopsis shichuana

Abstract: Four new eremophilenolides, 1-4, have been isolated from the whole plant of Ligulariopsis shichuana. Their structures were elucidated by spectroscopic methods, including 2D NMR experiments. Structures of compounds 1 and 2 were unequivocally established by X-ray diffraction experiments. All of these sesquiterpenes have eremophilane skeletons with 7(11)-en-8(12) lactone units. Compounds 1 and 2 showed moderate antibacterial activities against E. coli and B. subtilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 6 publications
6
33
0
Order By: Relevance
“…
In our ongoing investigation into bioactive compounds from the genus Ligularia (Compositae) plants [1][2][3][4][5][6][7] we have studied the roots of Ligularia tongolensis (FRANCH) HAND-MAZZ collected in mountainous areas (altitude: 3600 m) in southwestern China. Ligularia tongolensis is used as a traditional folk medicine in China and its roots can reduce phlegm, relieve coughing and cure pulmonary tuberculosis, urinary track blockages, common cold, and pharyngitis.
8)

However, the chemical constituents of this plant have not been reported up until now.

…”
mentioning
confidence: 99%
“…
In our ongoing investigation into bioactive compounds from the genus Ligularia (Compositae) plants [1][2][3][4][5][6][7] we have studied the roots of Ligularia tongolensis (FRANCH) HAND-MAZZ collected in mountainous areas (altitude: 3600 m) in southwestern China. Ligularia tongolensis is used as a traditional folk medicine in China and its roots can reduce phlegm, relieve coughing and cure pulmonary tuberculosis, urinary track blockages, common cold, and pharyngitis.
8)

However, the chemical constituents of this plant have not been reported up until now.

…”
mentioning
confidence: 99%
“…This is also the first report on the 13 C-NMR signal for a quaternary carbon at δ C 105.7, suggested that 1 has an eremophila-7(11)-en-12,8-lactone skeleton with an oxygened group at C-8. 13 Comparing its NMR data ( Table 1) to those of an analogous compound 3β-angeloyloxy-8β-methoxy-9β-senecioyloxyeremophila-7(11)-en-12,8α-lactone, 8 164.6) suggested the senecioxylxyl group location at C-9. The presence of hydroxy at C-6 could be deduced by the HMBC correlation H 3 -14 (δ H 0.96)/C-6 (δ C 69.9) and H-6 (δ H 5.02)/C-14 (δ C 20.1).…”
mentioning
confidence: 55%
“…1 H-, 13 C-NMR (DEPT) and 2D NMR were recorded on Bruker AVANCE 500 spectrometer with TMS as internal reference. HR-ESI-MS spectra were obtained on Bruker APEX II spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Among these compounds eremophilane sesquiterpenes stand out for several biological activities. [12][13][14][15] One member of this genus reported in the present study showed the notable ability to produce eremophilane sesquiterpenes, including two new in the literature, cupressolide A and cupressolide B. Due to the many biological activities shown by this class of compounds, this Xylaria deserves a careful study aiming to sesquiterpene production enhancement.…”
Section: Discussionmentioning
confidence: 91%